Hair cell synaptic dysfunction, auditory fatigue and thermal sensitivity in otoferlin Ile515Thr mutants. (11th October 2016) - Strenzke, Nicola; Chakrabarti, Rituparna; Al‐Moyed, Hanan; Müller, Alexandra; Hoch, Gerhard; Pangrsic, Tina; Yamanbaeva, Gulnara; Lenz, Christof; Pan, Kuan‐Ting; Auge, Elisabeth; Geiss‐Friedlander, Ruth; Urlaub, Henning; et al.
Abstract: The multi‐C2 domain protein otoferlin is required for hearing and mutated in human deafness. Some OTOF mutations cause a mild elevation of auditory thresholds but strong impairment of speech perception. At elevated body temperature, hearing is lost. Mice homozygous for one of these mutations, Otof I515T / I515T, exhibit a moderate hearing impairment involving enhanced adaptation to continuous or repetitive sound stimulation. In Otof I515T / I515T inner hair cells (IHCs), otoferlin levels are diminished by 65%, and synaptic vesicles are enlarged. Exocytosis during prolonged stimulation is strongly reduced. This indicates that otoferlin is critical for the reformation of properly sized and fusion‐competent synaptic vesicles. Moreover, we found sustained exocytosis and sound encoding to scale with the amount of otoferlin at the plasma membrane. We identified a 20 amino acid motif including an RXR motif, presumably present in human but not in mouse otoferlin, which reduces the plasma membrane abundance of Ile515Thr‐otoferlin. Together, this likely explains the auditory synaptopathy at normal temperature and the temperature‐sensitive deafness in humans carrying the Ile515Thr mutation. Synopsis: The Ile515Thr and the pachanga (Pga) mutations in otoferlin reduce the levels of otoferlin in auditory inner hair cells. Only the Pga mutation disturbs the plasma membrane abundance of otoferlin, which scales with spike rates in spiral ganglion neurons. Otoferlin is critical for synaptic vesicle reformation from bulk‐endocytosed membrane. Sustained IHC exocytosis and sound encoding depend on the amount of otoferlin at the plasma membrane, which can be reduced by mutations and/or elevated temperature. Increased adaptation at IHC synapses and delayed recovery explain auditory fatigue due to otoferlin mutations. An RXR motif presumably present in human but absent from mouse cochlear otoferlin further reduces the plasma membrane‐bound fraction of Ile515Thr‐otoferlin, thereby providing a molecular mechanism for the fever‐induced deafness in humans. Abstract : A mouse model of the human otoferlin Ile515Thr mutation provides insight into auditory synaptopathy at normal temperature and temperature‐sensitive deafness in humans carrying this mutation.